Estimation of roughness‐induced scattering losses in III‐nitride laser diodes with a photoelectrochemically etched current aperture. Issue 4 (20th January 2016) - Megalini, Ludovico; Shenoy, Renuka; Rose, Kenneth; Speck, James P.; Bowers, John E.; Nakamura, Shuji; Cohen, Daniel A.; DenBaars, Steven P.
Abstract : We estimate the roughening‐induced scattering optical losses in III‐nitride current aperture laser diodes (CA‐LDs) caused by imperfect photoelectrochemical (PEC) etching of the active region of a ( 20 2 ¯ 1 ¯ ) InGaN multi quantum well (MQW) laser diode. Roughness data were obtained by atomic force microscope (AFM) and scanning electron microscope (SEM) image processing of the remnant PEC‐etched waveguides after the top p‐layers were removed by focused ion beam cuts. Roughness (correlation length) values of ∼60 (∼600) nm have been measured that cause optical loss in the range of ∼8 cm −1 as estimated by using the 3D volume current method (VCM). Larger and more irregular bends contribute more significantly to the scattering loss. Extraction of the roughness (red line) from one edge of the remnant photoelectrochemical (PEC) etched active region of current aperture laser diode (CA‐LD) by image processing after the p‐epilayers were removed by focused ion beam (FIB).